TEST OF ANTIOXIDANT CONTENT IN BLUE LOTUS (Nymphaea Stellata Wild) LEAVES WITH DPPH METHOD (1,1-Diphenyl-2-Picrylhydrazyl) - Beta Herilla Sekti (Jurnal Jamu Kusuma, 2021)
Antioxidants are compounds materials that can inhibit the rate of oxidation of other molecules or neutralize free radicals. Antioxidants can be obtained in synthetic or natural forms. Natural antioxidants can protect the human body from damage to active oxygen which can inhibit degenerative diseases and inhibit the production of fat and food. Natural antioxidants can be obtained from plants, one of which is the Blue Lotus Plant (Nymphaea Stellata Wild). To ensure the presence of antioxidants in this plant, the antioxidant activity was tested using the DPPH method. The DPPH method was used to determine the free radical scavenging activity of the Ethanol Extract of Blue Lotus Leaf (Nymphaea Stellata Wild). The positive control used was Ascorbic Acid. The IC50 value obtained for testing the antioxidant content of blue lotus leaf is 78.405 ppm ± 24.607. And Ascorbic Acid 2,238 ppm. It can be concluded that the antioxidant activity of Blue Lotus Leaf is not too different from the positive control of ascorbic acid. The antioxidant activity of blue lotus leaf was stated to be strong and ascorbic acid was stated to be very strong. Keywords: Antioxidant, Free radicals, DPPH